Peningkatan Kapasitas Manajerial SDM Koperasi Simpan Pinjam di Kabupaten Bandung - Nurhayat Indra (E-Coops-Day, 2023)
Implementation of Community Service through training on Increasing the Managerial Capacity of Savings and Loan Cooperative HR Managers in Bandung Regency, especially in the material for preparing the KJK/KJKS strategic plan as one of the competency units for KJK/KJKS managers aims to improve competency both knowledge, attitude, and skills of cooperative managers in accordancewith SKKNI-BNSP standards, which will be ready to take the competency test. The training method is carried out using a module-based technical guidance method and working papers with the competency unit code KJK.SP01.006.01- Developing Strategic Planning. The results of the training evaluation of learning outcomes in increasing the competence of participants are still not optimal.